Ferrielectric properties and hysteresis loops of a Blume–Capel of core–shell with mixed spins: Monte Carlo study. (2nd September 2021) - Sahdane, T.; Masrour, R.; Jabar, A.
ABSTRACT: The ferrielectric properties of a ferrielectric of core–shell are studied using the Blume–Capel Ising (BCI) model with mixed spins Sa =5/2, Sb =1, and Sc =3/2 via Monte Carlo method. The effects of external longitudinal electric (EZ ) and crystal anisotropy Da, Db and Dc fields have been investigated. In addition, the variation of total and partial polarizations as a function of exchange coupling interactions ( Jaa, Jbb, Jcc, Jab, and Jbc ), crystal and external fields was discussed. Finally, the influence of the exchange interactions on the compensation and critical temperatures of the system and hysteresis cycles has been examined.